Characterization of Changes in Subchondral Bone Tissue Density of the Ankle Joint in Taekwondo Players - Xu, Guanghua; Liu, Hongyu; Zhang, Lifu (Frontiers in Bioengineering and Biotechnology, 2022)
Background： It has been found that ankle joint impingement can cause articular cartilage injury, and the change of subchondral bone density and distribution under long-term stress loading can reflect the stress interaction of the articular surface, the difference of bone remodeling degree, and predict the location of cartilage injury. Objective: To investigate the bone density distribution pattern of ankle joint subchondral bone under mechanical stress loading of taekwondo, the volume proportion of bone tissue with different bone densities, and the distribution characteristics of bone remodeling position. Study deign： controlled laboratory study Methods： Computed Tomography data were collected from the feet of 10 normal subjects (control group) and 10 high-level taekwondo athletes. Firstly, the distribution pattern of high density area of articular surface was determined by computed tomography osteoabsorptiometry and nine-grid anatomical region localization method. Secondly, the percentage of bone volume (%BTV) and the distribution trend of bone tissue were measured. Result： In the present study, it was found that there were high density areas in the 1st, 2nd, 3rd, 4th, 6th, 7th and 9th regions of the distal tibia of taekwondo athletes, and the distribution track was consistent with the high density areas of the talar dome surface (1st, 2nd, 3rd, 4th, 6th, 7th and 9th regions). At taekwondo , the percentage of bone tissue volume in distal tibia and talus with high and moderate bone density was significantly higher than that in control group(P < .05). Conclusion： The impact stress, ground reaction force, intra-articular stress, lower limb movement technology, lower limb muscle and tendon stress caused by Taekwondo lead to special pressure distribution pattern and bone tissue remodeling in the ankle.